Adaptive boosting with SVM classifier for moving vehicle classification - Norasmadi, Abdul Rahim; Abd Hamid, Adom, Prof. Dr.; Paulraj, Murugesa Pandian (Elsevier Ltd, 2013)
Link to publisher's homepage at http://www.elsevier.com/